Penggunaan Presupposisi pada Konten Friends of Merry Riana di YouTube: Penelitian - Salwa Fitri Hadju; Dakia N. Djou; Nuramila (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
Presupposition is part of pragmatic studies that refers to assumptions that are considered correct by the speaker or listener before producing a speech. Presuppositions play an important role in shaping the audience's understanding of the message conveyed by the speaker. Along with the development of digital media, especially YouTube, the study of presuppositions is increasingly relevant because this platform is often used to convey ideas, opinions, and information widely. Therefore, this study aims to describe the types of presuppositions, language functions, and speech intent contained in the content of "Friends of Merry Riana" on YouTube. This study uses a qualitative descriptive method with data collection techniques in the form of documentation, listening, and recording. The data in the study was in the form of speech containing presuppositions on the content of "Friends of Merry Riana" on YouTube which came from a video titled Gandi Sulistiyanto: Formerly a Driver, Now an Advisor to President Jokowi. Data analysis was carried out using the Miles and Huberman interactive model. The results showed that there were six types of presuppositions and sixlanguage functions in speech on the "Friends of Merry Riana" content on YouTube. The function of language that is widely found is the referential function because many speeches convey information or something that is intended. The purpose of speech is to convey information, build emotional closeness, and influence the audience's perspective.